Peran Tata Letak Tempat Duduk Siswa Dalam Mengelola Suasana Kelas di Lingkungan Sekolah Dasar Bunda Wacana - Septiana, Vera; Wijayanto, Sukma (Prosiding University Research Colloquium, 2021)
The study aims to find out how seating affects the atmosphere of grade school. It’s a qualitative study. This research source is the fourth grade teacher of the mother of the wacana mageagle. Data collection techniques are observation and interview. Haisl’s research was that class management was performed by the teacher first to configure seating positions, classroom decorations, and class hygiene. The teacher performs oversight on the performance of each student’s duties. After that it covered the students’ learning efficiency after the sit-sit was changed and the previous.